Landscape of Enhancer-Enhancer Cooperative Regulation during Human Cardiac Commitment - Hong Chen; Jun Xiao; Tingting Shao; Li Wang; Jing Bai; Xiaoyu Lin; Na Ding; Yinwei Qu; Yi Tian; Xiang Chen; Hui Liu; Hongyu Liu; et al. (Elsevier, 2019)
Although accumulating evidence has demonstrated the key roles of enhancers in gene expression regulation, the contribution of genome-wide enhancer-enhancer interactions to developmental decisions remains unclear. Here we explored the cooperative regulation patterns among enhancers to understand their regulatory mechanism. We first filtered robust enhancers in embryonic stem cells (ESCs) through integrating bidirectional transcription, genomic location, and epigenetic modification. Genome-wide enhancer-enhancer interactions were then identified based on enhancer-promoter relationships that were derived from Hi-C data. We further explored the interacting principles of the identified enhancer-enhancer interactions. The results revealed that the observed cooperativity occurred mainly between enhancers distributed within a 1-kb to 10-Mb distance across the genome. In addition, enhancer-enhancer pairs had higher expression correlations than non-interacting pairs. Finally, we identified robust enhancers during human cardiac commitment, and we found that enhancers exhibited strong stage-specific expression patterns. We further inferred the enhancer-enhancer interactions based on RNA sequencing (RNA-seq) data in heart development, according to the regulatory principles characterized from Hi-C data. The identified enhancer-enhancer interaction networks (EEINs) presented highly dynamic linkages. Moreover, enhancers cooperatively targeted many marker genes in each developmental stage to regulate stage-specific functions, which contribute to the organization of cell identity in heart development. Our work will increase the understanding of enhancer regulation in human heart development. Keywords: enhancer, eRNA, histone modification, cooperative regulation, heart development, Hi-C, RNA-seq